Shared Mechanisms of Neurodegeneration in Alzheimer's Disease and Parkinson's Disease. (12th May 2014) - Xie, Anmu; Gao, Jing; Xu, Lin; Meng, Dongmei
Abstract : Alzheimer's disease (AD) and Parkinson's disease (PD) have markedly different clinical and pathological features, but these two diseases are the most common neurodegenerative disorders. Previous studies have showed that there are common mechanisms in AD and PD. Several genetic studies have revealed mutations in genes associated with the risk of AD and PD. Circumstantial evidences have shown that dysregulation of brain iron homeostasis leads to abnormal iron accumulation and results in AD as well as PD. α -Synuclein and tau take part in the mechanisms of these diseases by oxidative stress and mitochondrial dysfunction. Some studies indicated that the loss of LC noradrenergic neurons may occur early in the progression of AD and PD. Nicotinic acetylcholine receptors (nAChRs) are members of the Cys-loop superfamily of pentameric ligand-gated ion channels; some evidence showed that nicotinic receptors may be associated with AD and PD. These experimental and clinical studies may provide a scientific foundation for common shared mechanisms in AD and PD.